A new high performance novolac-based polytriazole resin. (February 2018) - Ye, Lvyuan; Wan, Liqiang; Huang, Farong
A novolac-based polytriazole (NPTA) resin was synthesized using 4, 4′-diazidomethylbiphenyl and a propargylated novolac resin through catalyst-free click polymerization. Differential scanning calorimetry and Fourier transform infrared analysis results demonstrate that the NPTA resin can be cured at 80°C. The glass transition temperature of the cured NPTA-88 resin is 202°C. The thermal degradation temperature of the cured NPTA resin is 352°C under nitrogen. The composite of the resin exhibits good mechanical property.